Systematics of the low-energy electric dipole strength in the Sn isotopic chain - M. Markova; P. von Neumann-Cosel; E. Litvinova (Physics Letters B)
We present a systematic study of the mass dependence of the low-energy electric dipole strength (LEDS) in Sn isotopes in the range A=111−124 based on data obtained with the Oslo method and with relativistic Coulomb excitation in forward-angle (p,p′) scattering. The combined data cover an energy range of 2−20 MeV which permits, with minimal assumptions, a decomposition of the total strength into the contribution from the low-energy tail of the isovector giant dipole resonance (IVGDR) and possible resonance-like structures on top of it. In all cases, a resonance peaked at about 8.3 MeV is observed, exhausting an approximately constant fraction of the Thomas-Reiche-Kuhn (TRK) sum rule. For heavier isotopes (A≥118) a consistent description of the data requires the inclusion of a second resonance centered at 6.5 MeV, representing the isovector response of the pygmy dipole resonance (PDR). Its strength corresponds to a small fraction of the total LEDS only and shows an approximately linear dependence on mass number. The experimental results are compared to microscopic calculations to investigate the importance of an inclusion of quasiparticle vibration coupling (qPVC) for a realistic description of the LEDS. A possible interpretation of the experimentally observed two-bump structure is given.